1-Dimensional numerical modelling of unsaturated water flow and oxygen diffusion in overburden material column using hydrus 1-D. Issue 1 (November 2021) - Jarwinda,; Badhurahman, A; Kusuma, G J; Gautama, R S
Abstract: Coal mining activities, especially overburden material dumping can cause a negative impact into the environment, i.e., acid mine drainage, Acid mine drainage is characterized as low pH water with high sulphate and metal content produced from sulphidic-bearing overburden material with oxygen and water. In unsaturated condition, both of gaseous and water phases exist, acid mine drainage is generated. This study aims to characterize and model the water content in unsaturated condition and diffusion of oxygen of overburden material using the Hydrus 1-D software in a laboratory-scaled column. Laboratory-scaled column is initially filled with 75-cm height of dry overburden material and subjected into 5-cm constant head water level at the top of the column with free-flow condition at the bottom of column. The modelling result shows the water content of overburden material varies within depth and time elapsed and is saturated between 32400 minutes and 36000 minutes after initial wetting. Diffusivity of oxygen is linearly correlated with the water content of the overburden material at any given time and depth that varies between 1.34 × 10 −7 m 2 /s and 8.80 × 10 −12 m 2 /s. Water content and diffusivity of oxygen is expected to affect the generation of acid mine drainage in the overburden material.